Congruence Of Record Keeping of Tuberculosis Patients by Field Interviews in A Community Block of District Amritsar - Pooja Sadana; Vishal Verma; Tejbir Singh; SS Deepti (Medsci Publications, 2016)
Introduction: Good recording practices are necessary for effective patient management. When high-quality data are available, success can be documented and corrective actions taken to address problems that are identified. Objective: To assess the accuracy of record keeping of TB patients by field interviews Methods: The study was conducted on a total of 326 patients residing in the area of PHC Verka and registered with District Tuberculosis Centre, Amritsar. House to house visits were done. Outcome of the patient according to the TB register and according to interview were compared. Results: According to record out of 228 patients, the outcome of 105(46.10%), patients was cured, 105(46.10%) patients had completed their treatment, 10(4.40%) had defaulted, 6(2.6%) were failure and 2(0.9%) had transferred out. On interviewing the patients the outcome of 98(43%) was cured, 95(41.70%) were treatment completed, 29(12.70%), defaulted and 6(2.6%) were failure. Discrepancies were found between outcome recorded on TB register and as obtained on interviewing the patient. The treatment outcome according to record and outcome according to interview, was found to be statistically significant (p=0.005) Conclusion: Present study reveals that there is an urgent need to strengthen performance of the programme by proper record-keeping and efficient supervision by district health officials.